PENINGKATAN KETERAMPILAN MEMBACA PUISI SISWA KELAS IV DENGAN MODEL DEMONSTRASI DIDUKUNG MEDIA VIDEO PEMBELAJARAN DI SDN 1 SUMBERSARI KOTA MALANG - Yolanda Dana Kumala Sari; Lise Chamisijatin; Budi Santoso (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2019)
The purpose of this study is to improve poetry reading skill of 4th grade students at SDN Sumbersari 1 in Malang City, to know the activities of the teacher and students. This type of this research is classroom action research. This classroom action research model uses the Kemmis And Mc Taggart model which consist of four steps or stages in conducting classroom action research, namely: planning, action, observation, and reflection. The result of the study show an increasing activity of the teacher and students. The result of this study are flows. (1) Pre-action, from 25 students, only 5 students or 20% of the total students are able to read poetry well and correctly, while 20 students or 80% of students experience difficulty in reading poetry with an average poetry reading skill of 54.56%. (2) Cycle I, the percentage of teacher activity reached 83% with very good predicate, the percentage of teacher activity reached 83% with very good predicate, the percentage of student activity was 83% with very good predicate, and classical learning completeness was 78.8% (3) Cycle II, the percentage of teacher activity reached 86% with very good predicate, the percentage of students is 87% with